TAXA DE LOTAÇÃO EM DIFERENTES MODELOS DE CARROCERIA E SUA RELAÇÃO COM HEMATOMAS EM CARCAÇAS BOVINAS - FERREIRA, Kethylleen de Carvalho; FURTADO, Aline Correia; PIAZZON, Cleiton José; ESCOBAR, Loraine Saldanha; FLORES, Hugo Pereira; OLIVEIRA, Dalton Mendes de (ANAIS DO ENIC, 2018)
-